IMPACT OF EMPLOYEE ENGAGEMENT AND JOB SATISFACTION: A CASE STUDY OF SELECTED MULTISPECIALTY HOSPITALS AT HASSAN CITY - Savitha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The current scenario the business organizations are facing intense competition and challenges, the role of employees and their dedication towards the work has been one of the critical factors of concern for the business organization. In this connection this study mainly analyzes the relationship between employee work engagements between levels of job satisfaction in Multispecialty hospitals. In this study data has been collected through issuing of self-administrated structured questioner to the 150 employees (Nurse and doctors) of selected three popular Multi specialty hospitals in Hassan City. The researcher used to collect the data from the employees used porters five force model and binary style of collecting opinion of the respondents through using Google form and also conduct personal interview of the employees sharing their views about job satisfaction in hospital industry.The researcher used for data analysis for various statistical tools to identify the correlation between the employee work commitment and level of job satisfaction. The findings were identified that employee engagement is essential for especially for hospital sector how the satisfaction of the employees can affect their work performance, which has a direct link to the overall organization performance. It will reflect to the improve the quality of services provided by the Multispecialty Hospitals. Lastly this study recommends that today work commitment is most important in-service sector to increasing the employee work performance, the hospital should concentrate on employee’s welfare and developing a scientific performance appraisal system with sincere appreciation, rewards and recognition, then it will enhance employee job satisfaction in Hospital sector.